Placing names conversion into verbs as a mean of explaning their outstanding properties - PUPYNINA, E.V.; PROKHOROVA, O.N.; CHEKULAI, I.V.; BEKH, E.F. (Utopía y Praxis Latinoamericana, 2019)
ABSTRACTVerbs formed from toponyms by zero conversion are the focus of this article. The paper intends to show that converting a place name into a verb is a prominent way of explicating the place's salient properties. The data were collected from the corpora and detected on news, media sites and blogs. The study shows that verbs formed from place names demonstrate how people conceptualize places. Research shows that the linguistic salience is preceded by the conceptual salience that occurs when some striking event, fact, point of view about the place becomes strongly associated with it and regularly talked about. RESUMENLos verbos formados a partir de topónimos por conversión cero son el foco de este artículo. El artículo pretende mostrar que convertir un nombre de lugar en un verbo es una forma destacada de explicar las propiedades más destacadas del lugar. Los datos fueron recolectados de los corpus y detectados en sitios de noticias, medios y blogs. El estudio muestra que los verbos formados a partir de nombres de lugares demuestran cómo las personas conceptualizan los lugares y la relevancia lingüística está precedida por la importancia conceptual que ocurre cuando algún evento llamativo, el hecho sobre el lugar se asocia fuertemente con él.